Design, synthesis, molecular docking, and in vitro studies of 2-mercaptoquinazolin-4(3H)-ones as potential anti-breast cancer agents - Manal A. Alossaimi; Yassine Riadi; Ghaida N. Alnuwaybit; Shadab Md; Huda Mohammed Alkreathy; Engy Elekhnawy; Mohammed H. Geesi; Safar M. Alqahtani; Obaid Afzal (Elsevier, 2024)
Triple-negative breast cancer (TNBC) comprises 10 % to 20 % of breast cancer, however, it is more dangerous than other types of breast cancer, because it lacks druggable targets, such as the estrogen receptors (ER) and the progesterone receptor (PR), and has under expressed receptor tyrosine kinase, ErbB2. Present targeted therapies are not very effective and other choices include invasive procedures like surgery or less invasive ones like radiotherapy and chemotherapy. This study investigated the potential anticancer activity of some novel quinazolinone derivatives that were designed on the structural framework of two approved anticancer drugs, Ispinesib (KSP inhibitor) and Idelalisib (PI3Kδ inhibitor), to find out solutions for TNBC. All the designed derivatives (3a-l) were subjected to extra precision molecular docking and were synthesized and spectrally characterized. In vitro enzyme inhibition assay of compounds (3a, 3b, 3e, 3 g and 3 h) revealed their nanomolar inhibitory potential against the anticancer targets, KSP and PI3Kδ. Using MTT assay, the cytotoxic potential of compounds 3a, 3b and 3e were found highest against MDA-MB-231 cells with an IC50 of 14.51 µM, 16.27 µM, and 9.97 µM, respectively. Remarkably, these compounds were recorded safe against the oral epithelial normal cells with an IC50 values of 293.60 µM, 261.43 µM, and 222 µM, respectively. The anticancer potential of these compounds against MDA-MB-231 cells was revealed to be associated with their apoptotic activity. This was established by examination with the inverted microscope that revealed the appearance of various apoptotic features like cell shrinkage, apoptotic bodies, and membrane blebbing. Using flow cytometry, the Annexin V/PI-stained cancer cells showed an increase in early and late apoptotic cells. In addition, DNA fragmentation was revealed to occur after treatment with the tested compounds by gel electrophoresis. The relative gene expression of pro-apoptotic and anti-apoptotic genes revealed an overexpression of the P53 and BAX genes and a downregulation of the BCL-2 gene by real-time PCR. So, this work proved that compounds 3a, 3b, and 3e could be developed as anticancer candidates, via their P53-dependent apoptotic activity.